Assessing knowledge, motivation and perceptions about falls prevention among care staff in a residential aged care setting - Hang, J.; Francis-Coad, J.; Burro, B.; Nobre, D.; Hill, Anne-Marie (Mosby, Inc., 2016)
Falls are a serious problem in residential aged care settings. The aims of the study were to determine the feasibility of surveying care staff regarding falls prevention, and describe care staff levels of knowledge and awareness of residents' risk of falls, knowledge about falls prevention, motivation and confidence to implement falls prevention strategies. A custom designed questionnaire was administered to care staff at one site of a large residential aged care organization in Australia. The survey response was 58.8%. Feedback from staff was used to inform the administration of the survey to the wider organization. Seven (29.2%) care staff reported they were unsure or thought residents were at low risk of falls. Only five (20.8%) care staff were able to suggest more than three preventive strategies. These preliminary findings suggest that education to change care staff behavior regarding falls prevention should target improving care staff knowledge and awareness of falls.